Mast Cells in Neurodegenerative Disease - Jones, Michael K.; Nair, Archana; Gupta, Mihir (Frontiers in Cellular Neuroscience, 2019)
Neurodegenerative diseases affect millions of people worldwide, yet there are currently no effective treatments. Because risk of neurodegenerative disease substantially increases with age, greater life expectancy with a concomitant aging population means more individuals will be affected in the coming decades. Thus, there is an urgent need for understanding the mechanisms driving neurodegenerative diseases in order to develop improved treatment strategies. Inflammation in the nervous system, termed “neuroinflammation,” has become increasingly recognized as being associated with neurodegenerative diseases. Early attention focused primarily on morphological changes in astrocytes and microglia; however, brain and CNS resident mast cells are now receiving attention as a result of being ‘first responders’ to injury. Mast cells also exert profound effects on their microenvironment and neighboring cells including behavior and/or activation of astrocytes, microglia and neurons, which, in turn, are implicated in neuroinflammation, neurogenesis and neurodegeneration. Mast cells also affect disruption/permeability of the blood brain barrier enabling toxin and immune cell entry exacerbating an inflammatory microenvironment. Here we discuss the roles of mast cells in neuroinflammation and neurodegeneration with a focus on development and progression of four prominent neurodegenerative diseases: Alzheimer’s Disease, Parkinson’s Disease, Amyotrophic Lateral Sclerosis and Huntington’s Disease.